SARS-CoV-2 (COVID-19) Pandemic Remains a Global Public Health Threat - Mahendra Pal; Mati Roba Bulcha; Milsan Getu Banu; Dimitri Ketchakmadze (Zenodo, 2021)
Recently, an upsurge in the incidence of several emerging infectious diseases is causing great challenges to the health professionals throughout the globe. Since early 2020, an outbreak of coronavirus disease 2019 (COVID-19), now a pandemic, is hitting the world severely. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), causative agent of COVID-19, gain entry through the respiratory systems (nasopharyngeal) route causing infection. This disease is reported from all continents except Antarctica and it most commonly affects the lungs rather than the other organs. In affected person, pneumonia, cough, sore throat, dyspnea, fever, headache, and rhinorrhea is the main symptoms of COVID-19. There are different investigation methods to diagnose a patient suspected of COVID-19 like radiography and different laboratory technique like RT-PCR, which remains the investigation of choice. Social distancing, practicing hand hygiene, and use of facemask are mandatory to prevent the disease. Many of the drug trials are underway with the recent FDA approval of remdesivir. Very recently, immunization programme against COVID-19 is going on in many countries of the world. However, the efficacy and safety of the vaccines are not yet fully established.